2011
DOI: 10.1590/s1806-66902011000300015
|View full text |Cite
|
Sign up to set email alerts
|

Métodos e temperaturas de hidratação na qualidade fisiológica de sementes de milho

Abstract: Resumo -O procedimento de uniformização e elevação do teor de água das sementes é recomendável para se obter resultados uniformes e confiáveis, em testes para a qualidade fisiológica de sementes, como o envelhecimento acelerado e a deterioração controlada. O trabalho teve como objetivo avaliar a qualidade fisiológica de sementes de milho, após a hidratação sob diferentes métodos e temperaturas, visando à elevação do teor de água para 15; 20 e 25%. Empregou-se o delineamento inteiramente casualizado, em esquema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
1
5
0
3
Order By: Relevance
“…In a study of four hydration methods (wet substrate, humid atmosphere, immersion in water and addition of the amount of water required) to raise the moisture content of corn seeds, Zucareli et al (2011) found that the humid atmosphere method reduced the physiological potential of the seeds, corroborating the results obtained for the different characteristics assessed in the present study. On the other hand, the authors found that a temperature of 30 °C and the method of direct immersion in water did not alter the physiological quality of ordinary corn seeds, being suitable for the hydration of these seeds, diverging from the results of this study.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In a study of four hydration methods (wet substrate, humid atmosphere, immersion in water and addition of the amount of water required) to raise the moisture content of corn seeds, Zucareli et al (2011) found that the humid atmosphere method reduced the physiological potential of the seeds, corroborating the results obtained for the different characteristics assessed in the present study. On the other hand, the authors found that a temperature of 30 °C and the method of direct immersion in water did not alter the physiological quality of ordinary corn seeds, being suitable for the hydration of these seeds, diverging from the results of this study.…”
Section: Resultssupporting
confidence: 88%
“…In their study on the physiological potential of ordinary corn seeds after being submitted to hydration through the methods of humid atmosphere, wet substrate, immersion in water and addition of the required amount of water under two temperatures, 20 and 30° C, Zucareli et al (2011) found that the humid atmosphere method reduced the physiological quality of corn seeds and the method of direct immersion in water at 30º C did not impact the physiological quality of the seeds, being the most suitable for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Tabela 5 -Coeficiente de correlação de Spearman ( ) entre os dados médios obtidos nos testes de emergência de plântulas em campo e de germinação a baixa temperatura, dos lotes de sementes de milho, híbridos 30F35R e 30P70H *Significativo a 5% de probabilidade pelo teste T Temperaturas abaixo da ótima recomendada para germinação tornam o processo de embebição mais lento (ZUCARELI et al, 2011), podendo dificultar a reorganização das membranas celulares (CARVALHO et al, 2009), sendo este fato influenciado pela qualidade fisiológica (vigor) e genética (cultivar) da semente.…”
Section: Teste De Frio ----------------------------------------------unclassified
“…In general, higher electrical conductivity values occurred at the highest temperature (25 0 C), except for mother trees 6 and 12, in the lowest imbibition volume (75 mL) while leaching differences increased with the increasing imbibition period (Figure 1). Furthermore, the temperature is one of the factors affecting the leaching pattern of exudates, so that the quantity and speed of leachate loss are greater at higher temperatures (ZUCARELI et al, 2011). However, these authors reported that the observed changes do not grant a changing classification of seed lots.…”
Section: Resultsmentioning
confidence: 97%